2020
DOI: 10.2147/ott.s254925
|View full text |Cite|
|
Sign up to set email alerts
|

<p>The Potential Tumor Promotional Role of circVAPA in Retinoblastoma via Regulating miR-615-3p and SMARCE1</p>

Abstract: Background: Growing evidence reveals that circular RNAs (circRNAs) play roles in cancer development. However, the effects and possible mechanisms of circRNAs in retinoblastoma (RB) are far from clear. Methods: circVAPA expression pattern was identified by RT-qPCR. circVAPA induced effects on RB cells were tested by CCK-8, clone forming, flow cytometry and transwell assays. Bioinformatics assay, rescue experiments and dual-luciferase tests were applied for mechanism exploration. Additionally, mouse models were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…After studying the mechanism, he found that miR-615-3p can reverse the RB cell effect induced by circVAPA, and circVAPA positively regulates the downstream oncogene SMARCE1 through miR-615-3p. In addition, in vivo nude mice tumor formation experiments confirmed this finding [ 40 ]. Xing et al found that the down-regulation of the circular RNA hsa_circ_0001649 indicates that the prognosis of retinoblastoma is poor, and it regulates cell proliferation and apoptosis through the AKT/mTOR signaling pathway [ 41 ].…”
Section: Circrna and Common Smts In Childrenmentioning
confidence: 62%
“…After studying the mechanism, he found that miR-615-3p can reverse the RB cell effect induced by circVAPA, and circVAPA positively regulates the downstream oncogene SMARCE1 through miR-615-3p. In addition, in vivo nude mice tumor formation experiments confirmed this finding [ 40 ]. Xing et al found that the down-regulation of the circular RNA hsa_circ_0001649 indicates that the prognosis of retinoblastoma is poor, and it regulates cell proliferation and apoptosis through the AKT/mTOR signaling pathway [ 41 ].…”
Section: Circrna and Common Smts In Childrenmentioning
confidence: 62%
“…In addition, high expression of circ_0000527 and miR-1236-3p was significantly associated with advanced TNM stages, positive optic nerve invasion, and positive choroidal invasion in Rb patients [38]. Xu et al [36] found that the expression of circVAPA in Rb was closely related to tumor size, lymph node metastasis, and FIGO stage, and patients with a high expression level of circVAPA showed worse overall survival. In contrast, there are some circRNAs with low expression in Rb tissues.…”
Section: Circrnas As Prognostic Biomarkersmentioning
confidence: 98%
“…Furthermore, TET1-has_circ_0093996 might play a role in RB pathogenesis via regulating the TET1-circ_0093996/miR-183-PDCD4 axis [28]. In this context, circ_0000034, circ_0000527, circ_0119412, circ_0075804, circVAPA, and circFAM158A are significantly upmodulated in RB cell lines and tissues, whereas circ_0001649, circMKLN1, and circ_TET1 are expressed at low levels [30][31][32][33][34][35][36][37]. The roles of circRNAs in Rb include cellular and molecular mechanisms.…”
Section: Expression Of Circrnasmentioning
confidence: 99%
See 1 more Smart Citation
“…They further found that circDHDDS act as sponge of miR-361-3p, which promoted the proliferation of RB by regulating the expression of downstream Wnt3a gene. Xu’s study showed that circVAPA also increased in RB samples and cells, promoted RB cell proliferation through miR-615-3p/SMARCE1 axis, while the overexpression of miR-615-3p could inhibit the effect of circVAPA on RB cell proliferation [42]. S-phase kinase-associated protein 2 (SKP2) plays an accelerating role in various cancers.…”
Section: Circrna and Retinoblastomamentioning
confidence: 99%